2021
DOI: 10.1007/s11596-021-2418-y
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Subjective Visual Vertical in Diagnosis of Vestibular Migraine

Abstract: Objective To study the value of the subjective visual vertical (SVV) in the diagnosis of vestibular migraine (VM). Methods This study recruited 128 VM patients and 64 age-matched normal subjects. We detected the SVV during the interval between attacks in both groups, in sitting upright, and the head tilted at 45° to the left or right. We then examined the correlation between the SVV results with the vestibular evoked myogenic potential (VEMP) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It is commonly used to assess the otolith system particularly the utricle and can be a reliable marker of the degree of vestibular compensation after an acute vestibular deafferentiation. [ 19 20 ] There was no correlation of the SVV with VEMP latency and amplitude as was also seen in study by Mueller et al . [ 21 ] This is possible as both these tests measure different types of hair cell functions in the utricular macula.…”
Section: Discussionmentioning
confidence: 71%
“…It is commonly used to assess the otolith system particularly the utricle and can be a reliable marker of the degree of vestibular compensation after an acute vestibular deafferentiation. [ 19 20 ] There was no correlation of the SVV with VEMP latency and amplitude as was also seen in study by Mueller et al . [ 21 ] This is possible as both these tests measure different types of hair cell functions in the utricular macula.…”
Section: Discussionmentioning
confidence: 71%
“…To evaluate our question, additional work using previous classification systems was included for review, with the understanding that there are likely differences in patient identification. Previous studies evaluating static SVV performance in those with migraine and dizziness have found both appropriate 21 22 23 and inappropriate 24 25 mean tilt values with the head in the upright position. Specifically, Asai and colleagues 25 describe small cohort of patients with migraine, tension headache, and no headache, finding that those meeting criteria for migraine and tension headache demonstrated significantly greater mean SVV tilt than nonheadache patients.…”
Section: Tablementioning
confidence: 91%
“…Crevits et al 23 ) and inappropriate (Li et al 24 ; Asai et al 25 ) mean tilt values with the head in the upright position. Specifically, Asai and colleagues 25 describe small cohort of patients with migraine, tension headache, and no headache, finding that those meeting criteria for migraine and tension headache demonstrated significantly greater mean SVV tilt than non-headache patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation